Women Who Love: An Explorative Study on Experiences of Lesbian and Bisexual Women with a Mild Intellectual Disability in The Netherlands - Stoffelen, J. M. T. (Sex Disabil, 2018)
Empirical research that addresses sexual orientation in people with an intellectual disability (ID) is limited, and very little is known regarding the personal experiences of lesbian and bisexual women with ID. This study set out to answer the question: What are the experiences of lesbian and bisexual women with a mild intellectual disability in the Netherlands? Ten lesbian and bisexual women (average age of 33 years) with a mild intellectual disability took part in our study comprising of semi-structured interviews. Participants reported that they had found it hard to talk to others about sensitive subjects such as their sexuality, and had been left to figure out information regarding their sexual orientation without support or guidance. Our results point to a lack of information, sexual education and role models when it comes to lesbian sex and women with an intellectual disability. Social contact was often limited, and participants experienced difficulties finding a partner. Furthermore, participants often had to cope with mental health problems and had struggled with loneliness, depression and addiction. Last but not least, our participants reported that they had been discriminated against. Coming out (revealing your sexual orientation) is not easy when you have an intellectual disability. To enable women with ID who have lesbian or bisexual feelings to understand and secure their sexual rights in their daily lives is important. Therefore, it is necessary to provide support in the following domains: sexual education and training, social contact and assertiveness.